Localization and abundance of early markers of fat cell differentiation in the skeletal muscle of cattle during growth — Are DLK1-positive cells the origin of marbling flecks?. (February 2015) - Albrecht, Elke; Kuzinski, Judith; Komolka, Katrin; Gotoh, Takafumi; Maak, Steffen
Abstract: Localization and abundance of early markers of adipogenic differentiation were investigated in bovine muscle tissue to verify their association with marbling development. Bovine skeletal muscle samples were used for immunohistochemical localization and measurement of mRNA and protein abundance of delta-like homolog 1 (DLK1) and CCAAT/enhancer-binding protein beta (CEBPB). The localization of DLK1-positive cells confirmed the position of small clusters of adipocytes which can be considered as the origin of marbling flecks. The results indicated higher DLK1 expression in the less marbled muscle of Holstein (HS) steers ( P  < 0.05) and a trend to higher CEBPB expression in Japanese Black (JB) steers ( P  < 0.1) at slaughter. The number of DLK1-positive cells and fat content were negatively correlated. The lower expression of DLK1 together with higher CEBPB abundance during fattening in JB may have contributed to the development of more adipocytes in the skeletal muscle of JB. Highlights: Localization of DLK1-positive cells suggests association with origin of marbling flecks. DLK1 expression was increased in the less marbled muscle of Holstein (HS) steers. The number of DLK1-positive cells and fat content were negatively correlated. Expression pattern of DLK1 suggests an earlier down-regulation in JB. DLK1 and CEBPB abundances contribute to adipocyte development in skeletal muscle. DLK1 is involved in fat deposition and distribution over all body fat depots.